Simbol Perempuan dalam Kanji Jepang dan Mandarin - Harisal - Harisal; Elvira Septevany; dan dan Liu; Kanah Kanah; wahyuning dyah (Universitas Diponegoro, 2024)
Women are widely used in writing kanji, both Japanese and Mandarin kanji. The aim of this research is to describe the meaning of Woman in the kanji, both kanji in Japanese and Mandarin. The method used is a descriptive-qualitative research method, which is a method used by researchers to find knowledge or theory regarding research at a certain time, with the population and sample being kanji which uses female kanji originating from Japanese and Mandarin to get the meaning and describe it. The research results show that there are several similarities and differences in literal meaning in Japanese and Mandarin. However, the difference in meaning is not so significant because the interpretations are almost the same and the ultimate goal is to both represent women, so it can be seen that the meaning of women in kanji in both Japanese and Mandarin is both to represent women, both in terms of activities carried out and woman's own identity. <a href=